Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Dengan Metode Simple Additive Weighting di SMKN 5 Kota Tangerang - Ahmad Fauzi; Syahrial Amirullah; Rio Supriyanto (Jurnal ICT : Information Communication & Technology, 2021)
Schools are facilities created by the government to develop the potential that exists in humans through learning activities. To get a good school quality requires a teaching team that has good competence as well. To provide a motivation so that the teaching team is enthusiastic in providing teaching to students, the school will give a reward to teachers who excel. But in giving these rewards the school still uses the manual method so that in the selection of outstanding teachers it still takes a long time. Therefore, this research will try to provide an alternative for the school in deciding the teachers who excel in accordance with the criteria and methods used. In this study using the Simple Additive Weighting (SAW) method. In decision making, the Simple Additive Weighting (SAW) method is used in the selection of teachers who excel so that it will help the school in determining the teachers who excel. The results of the study were tested with TAM and got a score of 229 criteria. The results of the calculation will get a figure of 83.273%. The usability level of the application for selecting high-achieving teachers can be obtained a value of 83.27 %